Exploring the photocatalytic potential of copper iodide thin films deposited via multiple spray technique - Nisha Joseph; Tina Sebastian; Jilu C John; Alphonsa Paul; Jincemon Cyriac; Saji Augustine (Applied Surface Science Advances, 2024)
This study explores the optimization of deposition parameters for CuI thin films, and investigates their potential application as photocatalysts. γ-CuI thin films were grown on glass substrate using the nebulized spray method at different substrate temperatures. Structural, morphological, and optical studies of the films were carried out. The substrate temperature was found to have a profound influence in determining the aforesaid properties of the films. As seen from scanning electron micrographs, the morphology of the films varied from discontinuous to uniform, and then to being agglomerated, when substrate temperature was increased from 50 °C to 175 °C. At the same time, it was observed from x-ray diffraction studies that films with better crystallite size was formed at lower temperatures. To obtain films with good crystallinity as well as continuous morphology, multiple spraying was carried out which involve repeating the deposition process manifold on the same substrate. Systematic characterization showed that multiple spraying at low temperatures resulted in uniform films with good crystallinity. The photocatalytic activity of single, double and triple sprayed CuI thin films prepared by nebulized spray method under visible light irradiation was also investigated. All of the films exhibited photocatalytic activity in the visible spectral region, with the triple-sprayed CuI thin film exhibiting the greatest efficiency in the photocatalytic degradation of Methylene blue.